Thermoplastic starch nanocomposites reinforced with nanofibrillated cellulose: a study on processing and plasticization in the presence of water as a process plasticizer - Lipa, Annette Daphne Cochon (2024)
The effect of water on TPS preparation and properties is extremely relevant due to its hole as process plasticizer and desestruturation agent. Here we describe the investigation of the effect of residual water from nanofibrillated cellulose suspensions in the properties of cellulose/thermoplastic starch (TPS) composites. It was used corn starch, cellulose nanofibrils from eucalyptus and glycerol as plasticizer. The nanofibrillated cellulose used from its suspensions containing up to 4% solids was introduced directly to starch and glycerol and dried to residual water content of 15-25%. Excess water was removed prior to extrusion in an air circulation oven and processed with added glycerol (70 and 80% based on the dry weight of starch and glycerol) as the primary plasticizer and residual water acting as the processing plasticizer. The NFC content was 2.5, 5, 7.5, and 10% based on the dry weight of starchglycerol/NFC system. The results showed that all the formulations developed exhibited a significant reduction in moisture absorption as the NFC content increased. This effect was particularly pronounced in the formulation containing 20% glycerol and 10% NFC. Optical microscopy revealed a complete destructuring of the starch, evidenced by the absence of residual granules, a result that was further confirmed by scanning electron microscopy (SEM). The SEM analysis also demonstrated a remarkably homogeneous dispersion of the NFC within the matrix, with minimal agglomeration observed. The nanocomposites showed significant mechanical improvements across all formulations. At higher NFC concentrations, a transition from a ductile to a more brittle state was observed, with tensile strength doubling compared to formulations with lower NFC content, highlighting NFC\'s reinforcing capability despite reduced ductility. The developed material outperformed TPS without added water, exhibiting a lighter color and reduced thermal and chemical degradation. These findings confirm the effectiveness of the methodology and the essential role of residual water in material plasticization and structuring.